Draft Annual Plan, 1975-76 (Volume I) Government of Uttar Pradesh - Planning Commission (Planning Commission, 1975)
As in the rest of the country, the economy of the State continued to feel the impact- of inflationary pressures and shortage of essential goods during the year under review. On account of repeated failures of monsoon in 1971-72, 1972-73, 1973-74 and again in 1974-75 serious drought conditions persisted all through Apart from affecting agricultural production in unirrigated areas, even in the irrigated areas could not escape from the damage caused by the failure of monsoon.
Planning Department, Government of Uttar Pradesh